Ingestion of Ixodes keiransi (Acari: Ixodidae) by Peromyscus yucatanicus (Rodentia: Cricetidae): Registro de ingestión de Ixodes keiransi - Torres-Castro, Marco; Suárez-Galaz, Alejandro; Panti-May, Jesús Alonso; Sánchez-Montes, Sokani; Yam-Lozada, Andrea; Yeh-Gorocica, Aarón; Reyes-Novelo, Enrique; Colunga-Salas, Pablo; Aguilar-Tipacamú, Gabriela; Rodríguez-Vivas, Roger Iván (Therya Notes, 2025)
This paper aims to report the ingestion of Ixodes keiransi by Peromyscus yucatanicus. Fragments of two tick larvae were collected from the intestinal content of a P. yucatanicus captured in Yucatan, Mexico. Genetic material was obtained from both specimens, and a fragment of 400 bp of the 16S-rDNA gene was amplified and sequenced. Bioinformatics analyses were performed, and a phylogenetic tree was constructed to determine the identity of the collected ticks. Peromyscus yucatanicus is a wild rodent endemic to the Yucatan Peninsula. It carries vectorborne pathogens and the arthropods that transmit them. Its diet consists of different elements, including arthropods. However, this is the first report of this rodent’s ingestion of Ixodes keiransi. This tick is a biological vector of important public health pathogens, including Rickettsia and Borrelia. This finding opens questions and hypotheses about alternative enzootic transmission mechanisms of tick-borne pathogens through tick ingestion in endemic areas.